Global Perceptions of the Antarctic Treaty System - Bridgman, Sam (University of Canterbury, 2001)
The Antarctic treaty System (ATS) manages a large pan of the planet, an area larger then the U.S.A and Mexico combined. It is also a very important part of the worlds climate, potentially contains valuable minerals and provides immense scientific opportunities. The Antarctic region is important to the world politically, environmentally, economically and socially (Anon 1995c: 14). Combined these factors result in the ATS being closely scrutinised by those outside and within, to ensure that the Antarctic region is being managed for the best possible lesult. This literature review will analyse the past comments for and against the ATS, the rationale for the comments and in some cases the response Of the ATS to comments made. The Antarctic treaty System (ATS) manages a large pan of the planet, an area larger then the U.S.A and Mexico combined. It is also a very important part of the worlds climate, potentially contains valuable minerals and provides immense scientific opportunities. The Antarctic region is important to the world politically, environmentally, economically and socially (Anon 1995c: 14). Combined these factors result in the ATS being closely scrutinised by those outside and within, to ensure that the Antarctic region is being managed for the best possible lesult. This literature review will analyse the past comments for and against the ATS, the rationale for the comments and in some cases the response Of the ATS to comments made.